Perceived Social Support as Predictor of Acculturative Stress Among Indonesian Exchange Students in Europe - Fedolina, Beatrice Febe; Edilburga Wulan Saptandari, Edilburga (UIN Sunan Kalijaga, 2024)
Participating in international student exchange programs offers valuable experiences during higher education. However, adjusting to numerous changes can lead to acculturative stress. Previous research has highlighted the importance of perceived social support in reducing acculturative stress. This study aimed to explore whether perceived social support could predict acculturative stress among Indonesian exchange students in Europe, using a quantitative approach. The ASSIS (Acculturative Stress Scale for International Students) and the ISSS (Index of Sojourner Social Support) were used as data collection tools. The sampling technique used in this research was a non-random sampling technique-accidental sampling technique. Participants were Indonesian exchange students in Europe (N = 119) with the age range of 21-24 (x̄ = 21). Results showed that 74.79% of the students had high levels of perceived social support, and 63.02% of them had low levels of acculturative stress. Linear regression analysis proved that perceived social support could significantly predict 8.86% of students’ acculturative stress. Additionally, no significant difference was found between gender in both acculturative stress (p= .356) and perceived social support (p=.280). Broadening social networks during the exchange program period would prevent students from experiencing high levels of acculturative stress. Berpartisipasi dalam program pertukaran pelajar internasional menawarkan pengalaman berharga selama pendidikan tinggi. Namun, penyesuaian terhadap berbagai perubahan dapat menimbulkan stres akulturatif. Penelitian sebelumnya telah menyoroti pentingnya persepsi dukungan sosial dalam mengurangi stres akulturatif. Penelitian ini bertujuan untuk mengeksplorasi apakah dukungan sosial yang dirasakan dapat memprediksi stres akulturatif pada pelajar pertukaran Indonesia di Eropa, dengan menggunakan pendekatan kuantitatif. ASSIS (Acculturative Stress Scale for International Students) dan ISSS (Index of Sojourner Social Support) digunakan sebagai alat pengumpulan data. Teknik pengambilan sampel yang digunakan adalah teknik non random sampling-teknik accidental sampling. Pesertanya adalah pelajar pertukaran Indonesia di Eropa (N = 119) dengan rentang usia 21-24 tahun (x̄ = 21). Hasil penelitian menunjukkan bahwa 74,79% siswa memiliki tingkat persepsi dukungan sosial yang tinggi, dan 63,02% di antaranya memiliki tingkat stres akulturatif yang rendah.